Energy-saving analysis for the Modern Wing of the Art Institute of Chicago and green city strategies. (June 2017) - Wang, Xiaoxiao; Wang, Nan; Liu, Xiangfeng; Shi, Ruiting
Abstract: This article evaluates the energy performance of the Modern Wing of the Art Institute of Chicago and provides suggestions for optimizing its energy performance and the Leadership in Energy and Environmental Design (LEED) certification. The goal is to find a feasible way of improving the energy-saving rate based on the ASHRAE standard model, enhancing its resource efficiency by making full use of on-site renewable natural resources for expanding glass-curtain wall buildings, and integrating LEED-accredited features. Finally, it evaluates the possibilities of using alternative design schemes and innovative building technologies for updating this building and explores green city strategies and sustainable urban planning ideas taking Beijing and Shanghai as typical instances in the future.